Effect of Sintering Temperature on the Porosity and Mechanical Properties of (Ti-Zr) Scaffolds (Damascus University Journal for engineering sciences, 2023)
Powder Metallurgy Technology is considered an effective method for producing porous biomaterials, as this method allows to obtain the required porosity by controlling the compaction pressure or adding particles as the space holder. The Sintering process is one of the most important processes of Powder Metallurgy Technology, due to its direct impact on the properties of the product, as a result of the changes in the structure of the powder. Bone injuries often require the implantation of biomaterial to heal and recover the damaged bone. Porous Titanium alloys are widely used as implants in orthopedic applications, the mechanical properties of porous Titanium alloys should match those of natural bone in order to obtain a functionally satisfactory implant, and Titanium scaffolds must have a higher porosity from (40%). In this research, porous scaffolds were prepared from (70%wt Ti-30%wt Zr) by using Powder Metallurgy method, and the effect of sintering temperature on the porosity and compressive strength of (Ti-Zr) Scaffolds was investigated. The results showed that the value of the compaction pressure to be applied to obtain the required porosity of the (Ti-Zr) scaffolds is (1.5 Ton= 190.98 Mpa), as this value was determined experimentally, it was found that by increasing the sintering temperature the compressive strength of scaffolds decreased and their porosity increased. The experiments were conducted at the Higher Institute of Applied Sciences and Technology.
Keywords: Powder Metallurgy Technology; Sintering; Scaffolds